Public Space, Technology, and Humanity in Inclusion Education Policy Dynamics in Indonesia - Miftah, Muhammad; Choir, Abu (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
Discrimination in the education world is not only incidental under certain conditions. The injustice sometimes "deliberately" slips into policy products that are not accessible to all groups. Public space and humanity are important to formulating a humane and fair. Policy products that are ambiguous and insensitive to dynamic technological developments create uncertainty for policy executors in implementing policies in the field. This research dissects the products of inclusive education policies from time to time using the theory of power relations to find the dimensions of humanity, technology, and public space and capture the visible social impacts of the implementation of educational policies both in real space and virtual space. The findings of this research are: first, the existing policy products indirectly include elements of humanity in general, but on the other hand, they leave aside technological developments which are very dynamic. The two existing policy products do not provide input and evaluate the weaknesses and strengths of the implemented policies.